An Efficient Approach for Estimating Unknown Constants in an Adaptive Inventory Control System under Uncertainty. - Roy, Sushanta K.; Khan, Mohammad I. (Journal of Science, 2024)
This study focuses on inventory control in a manufacturing system for a typical machine building enterprise, involving machine building, transport, storage bunker, and assembly line. The storage bunker faces varying disturbances from the assembly line, necessitating consistent product flow from machining and transport to prevent operational failures. However, the lack of an exact machining model and uncertainties related to machine failures demand an adaptive decision-making system, which has already been developed. In this paper, we propose a modified, more realistic approach, to estimate some properties of the machining model more accurately, accounting for uncertainties due to machine failures and predictable, inconsistent disturbances from the assembly line. The effectiveness of this modified approach is demonstrated through simulation experiments.